Are Investors Influenced by the Order of Information in Earnings Press Releases? - Cheng, Lin; Roulstone, Darren T.; Van Buskirk, Andrew (The Accounting Review, 2021)
ABSTRACT We examine how the ordering of information within quarterly earnings announcements influences investor response to those announcements. Specifically, we examine whether earlier discussion of earnings information, and earlier discussion of qualitatively positive or negative information, is associated with stronger responses to that information. Controlling for the linguistic content of the earnings announcement, we find a positive relation between investor response to information and the prioritization of that information in the earnings announcement. We find no evidence of investor over-reaction and, to the contrary, find some evidence that investors under-react to prioritized information. Our evidence, in conjunction with experimental evidence in Elliott (2006), suggests that information placement influences investors' responses. However, unlike the experimental evidence in Elliott (2006), our archival results suggest that investor response to information placement is warranted, rather than the result of an unintentional cognitive effect. Data Availability: Data are available from the public sources cited in the text. JEL Classifications: G14; G41; M40.